2019
DOI: 10.1136/bmj.l5919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of new surgical treatments for benign prostatic hyperplasia: systematic review and network meta-analysis

Abstract: Objective To assess the efficacy and safety of different endoscopic surgical treatments for benign prostatic hyperplasia. Design Systematic review and network meta-analysis of randomised controlled trials. Data sources A comprehensive search of PubMed, Embase, and Cochrane databases from inception to 31 March 2019. Study selection Randomised controlled trials com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 34 publications
(36 reference statements)
3
56
0
9
Order By: Relevance
“…(2019) revealed EEP achieved better functional outcomes (Qmax and IPSS) than resection and vapourisation methods at 6 and 12 months post‐operatively, and the difference remained significant 24 and 36 months after the operation. While the criteria of enrolment were a little different across these studies and the present study, our results were generally in line with the findings of the above studies (Arcaniolo et al., 2019; Huang et al., 2019; Wroclawski et al., 2019), suggesting that EEP has become a new standard of the surgical treatment for BPH. There are some limitations in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…(2019) revealed EEP achieved better functional outcomes (Qmax and IPSS) than resection and vapourisation methods at 6 and 12 months post‐operatively, and the difference remained significant 24 and 36 months after the operation. While the criteria of enrolment were a little different across these studies and the present study, our results were generally in line with the findings of the above studies (Arcaniolo et al., 2019; Huang et al., 2019; Wroclawski et al., 2019), suggesting that EEP has become a new standard of the surgical treatment for BPH. There are some limitations in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…Enucleation of the prostate utilizes various laser technologies [Holmium-LEP (HoLEP), Thulium-LEP (ThuLEP), Greenlight-LEP (GreenLEP) and Diode-LEP (DiLEP)] to transurethrally enucleate the adenoma to allow for its removal from the capsule. In a recent meta-analysis that compared various laser enuclea tion, resection, and vaporization techniques with monopolar and bipolar TURP in 13 34 The worst performing method was diode laser vaporization [-1.90 (-5.07 to 1.27)]. IPSS at 12 months after treatment showed similar results.…”
Section: Aquablationmentioning
confidence: 95%
“…A 2005 review article has listed the incidence of several complications following radical prostatectomy: mortality <0.3%, impotence >50%, ejaculatory dysfunction 100%, orgasmic dysfunction 50%, incontinence <5%-30%, pulmonary embolism <1%, rectal injury <1%, urethral stricture <5%, and transfusion 20% (McCullough, 2005). In a 2019 systematic review and network meta-analysis, RE was reported in 17 out of 109 trials (Huang et al, 2019).…”
Section: What Is the Honest Reality?mentioning
confidence: 99%